Factors associated with food insecurity among pregnant women in Gedeo zone public hospitals, Southern Ethiopia - Areba, Abriham Shiferaw; Akiso, Denebo Ersulo; Haile, Arega; Abire, Belayneh Genoro; Kanno, Girum Gebremeskel; Tirore, Lire Lemma; Abame, Desta Erkalo (Frontiers in Public Health, 2024)
Background: Food insecurity refers to a lack of consistent access to sufficient food for active, better health. Around two billion people worldwide suffer from food insecurity and hidden hunger.This study focuses on food insecurity and associated factors among pregnant women in Gedeo Zone Public Hospitals, Southern Ethiopia.Method: An institutional-based cross-sectional study was conducted among pregnant women in Gedeo zone public hospitals from May to June 2021. Primary data of 506 pregnant women were collected using interviewer-administered structured questionnaire and a multi-stage sampling technique was used to select study participants. The household food insecurity access scale of the questionnaire was used and a woman was considered as food insecure when it has any of the food insecurity conditions mild, moderate, or severe food insecure, otherwise, it was classified as food secure. Adjusted odds ratio (AOR) and their 95% confidence intervals (CI) determined the association between various factors and outcomes.Results: Of all study participants, 67.39% of the women were food insecure, and the remaining 32.6% had food security. The pregnant women from rural areas [AOR=0.532, 95 % CI: 0.285, 0.994], married [AOR=0.232, 95% CI: 0.072, 0.750], had a secondary education [AOR=0.356, 95%CI: 0.154, 0.822], and be employed [AOR=0.453, 95% CI: 0.236, 0.872], the wealth index middle [AOR=0.441, 95% CI: 0.246, 0.793] and rich [AOR=0.24, 95 % CI: 0.128, 0.449] were factors associated with food insecurity.The study area had a high prevalence of food insecurity. Food insecurity was reduced in those who lived in rural areas, were married, had a secondary education, were employed, and had a wealth index of middle and rich.